2000
DOI: 10.1002/1097-0061(20000930)16:13<1229::aid-yea618>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

A network of proteins around Rvs167p and Rvs161p, two proteins related to the yeast actin cytoskeleton

Abstract: The Rvs161p and Rvs167p proteins of Saccharomyces cerevisiae, homologues of higher eukaryotes' amphiphysins, associate with actin and appear to be involved in several functions related to the actin cytoskeleton. In order to identify partners of the Rvsp proteins, yeast libraries constructed in two‐hybrid vectors were screened using either Rvs167p or Rvs161p as a bait. The selected candidates, representing 34 ORFs, were then tested against both Rvsp proteins, as well as domains of Rvs167p or Rvs161p. Among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 75 publications
3
46
0
Order By: Relevance
“…This indicates that the C-terminal sequences with the potential to form coiled-coils might fulfill a noncatalytic function in concert with sequences of the N-terminal half and affect proper localization and/or catalytic activity. Further functional analysis of the sequences outside the catalytic domain of Gyp5p would also be of interest, since previous studies suggested that the protein product of YPL249c (that we here identify to be the Ypt1-GAP Gyp5p) appears to interact with Rvs167p, a protein apparently involved in actin cytoskeleton function (39,40). In the case of Gyp1p of which a significant fraction is already bound to membranes, supposedly including the Golgi, the region N-terminal of the catalytic domain of Gyp1p is not re- quired to rescue, in synthetic media, a ⌬gyp1 deletion strain from growth inhibition at 37°C (34).…”
Section: Discussionmentioning
confidence: 95%
“…This indicates that the C-terminal sequences with the potential to form coiled-coils might fulfill a noncatalytic function in concert with sequences of the N-terminal half and affect proper localization and/or catalytic activity. Further functional analysis of the sequences outside the catalytic domain of Gyp5p would also be of interest, since previous studies suggested that the protein product of YPL249c (that we here identify to be the Ypt1-GAP Gyp5p) appears to interact with Rvs167p, a protein apparently involved in actin cytoskeleton function (39,40). In the case of Gyp1p of which a significant fraction is already bound to membranes, supposedly including the Golgi, the region N-terminal of the catalytic domain of Gyp1p is not re- quired to rescue, in synthetic media, a ⌬gyp1 deletion strain from growth inhibition at 37°C (34).…”
Section: Discussionmentioning
confidence: 95%
“…Genes whose products are involved in cell wall formation, maintenance, and regulation, including members of the PKC͞ mitogen-activated protein (MAP) kinase cell integrity sensing pathway, constitute the largest of the Pho85 synthetic lethal gene classifications. Of the 24 direct substrates (Table 1), 7 have known roles in cell wall formation, maintenance, and regulation (36)(37)(38)(39)(40) and͞or interact with elements of the PKC͞MAP kinase pathway (41)(42)(43)(44)(45)(46) (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that previous two-hybrid interactions between the BAR domain of Rvs167p and fulllength Rvs167p may have been indirect or an artifact of BAR domain overproduction. In support of this, Bon et al (2000) saw a two-hybrid interaction between Rvs167p and Rvs167p when both genes were on high-copy plasmids but not when they were on low-copy plasmids.We also tested whether Rvs161p could homodimerize. Because Rvs161p and Rvs167p are the only BAR-domaincontaining proteins in yeast and because Rvs161p is required for fusion during mating and Rvs167p is not (Brizzio et al, 1998), we were especially interested in whether Rvs161p would form homodimers in cells during the mating response.…”
mentioning
confidence: 80%